Empowering Students Through Journal Publication Workshops to Improve Academic Writing and Research Skills (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to enhance students’ understanding and readiness in publishing scientific articles through a journal publication workshop. The program was designed to improve academic writing literacy and motivate students to contribute to scholarly publications. A total of 15 participants attended the workshop, which involved interactive sessions on journal structures, submission processes, and publication ethics. Based on the evaluation results, the average overall score was 4.73 out of 5, indicating a very high level of participant satisfaction. The highest-rated aspects were relevance of materials (4.93) and new insights gained (4.93), followed by clarity of presentation (4.73) and motivation impact (4.73). Qualitative feedback revealed that participants felt the workshop provided valuable knowledge, boosted confidence, and helped them understand the publication process more effectively. Suggestions for improvement included providing written guidelines or booklets, incorporating case studies of accepted and rejected articles, and expanding the activity to reach more students. The results demonstrate that this workshop effectively empowers students in academic writing and fosters a stronger research and publication culture among undergraduates.